2016
DOI: 10.1037/edu0000125
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ emotional exhaustion is negatively related to students’ achievement: Evidence from a large-scale assessment study.

Abstract: Prior research has demonstrated that teachers' professional knowledge and motivation are strongly related to students' learning and motivation. Symptoms of teachers' stress and burnout (e.g., emotional exhaustion) are also thought to influence students' achievement, but no empirical study has tested this prediction. Using multilevel analyses and a representative sample consisting of 1,102 German elementary school teachers and their students, we addressed this gap in knowledge by examining the association betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
174
2
20

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(201 citation statements)
references
References 52 publications
5
174
2
20
Order By: Relevance
“…Moreover, not only are teachers leaving the field and reporting higher rates of emotional distress, but students are also feeling the effects of educator burnout. Research has suggested that teacher's feelings of stress and burnout are associated with student emotional well‐being and academic achievement (Becker, Goetz, Morger, & Ranellucci, ; Klusmann, Richter, & Lüdtke, ). Student behavior, such as vandalism, bullying, defiance, and talking back to teachers, is correlated to educator stress and burnout (Geving, ; Kokkinos, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, not only are teachers leaving the field and reporting higher rates of emotional distress, but students are also feeling the effects of educator burnout. Research has suggested that teacher's feelings of stress and burnout are associated with student emotional well‐being and academic achievement (Becker, Goetz, Morger, & Ranellucci, ; Klusmann, Richter, & Lüdtke, ). Student behavior, such as vandalism, bullying, defiance, and talking back to teachers, is correlated to educator stress and burnout (Geving, ; Kokkinos, ).…”
Section: Introductionmentioning
confidence: 99%
“…Students of teachers that are feeling burned‐out tend to cause more behavioral disruptions, be less motivated, and reach their academic goals less frequently (Jennings & Greenberg, ). Heightened emotional exhaustion is associated with decreased student growth, and lower scores on student's academic achievement tests as student's feelings of anger and enjoyment are related to their teacher's instructional behaviors (Becker et al, ; Klusmann et al, ). Educators that suffer from burnout have decreased classroom organization and a diminished ability to model emotional regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Experiencing high levels of stress is detrimental for teachers’ well‐being, their teaching behaviour quality, and retention (Harmsen, Helms‐Lorenz, Maulana, & van Veen, ; Hanif, ). Furthermore, teacher stress harms students’ achievement (Klusmann, Richter, & Lüdtke, ; Ronfeldt, Loeb, & Wyckoff, ).…”
Section: Introductionmentioning
confidence: 99%
“…Emotional exhaustion is a factor that causes a decline in teacher psychological well-being, in which emotional exhaustion is the main factor that causes a person to despair, give up and quit his job. Emotional exhaustion refers to stress dimension experienced by a person, including feelings of tense, depressed and decreasing the level of patience (Maslach et al, 2001), which ultimately has an adverse impact on student learning outcomes (Klusmann, Richter, & Lüdtke, 2016;Shen et al, 2015).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%